Value of neutrophil CD64 index in the etiological diagnosis of community-acquired pneumonia in children - XU Lei, LIU Xiaomeng, SUN Caihong, ZHANG Mengxue, QU Zhenghai (精准医学杂志)
Objective To investigate the value of neutrophil CD64 (nCD64) index in the etiological diagnosis of community acquired pneumonia (CAP) in children. Methods A total of 108 children with CAP who were hospitalized in our hospital from November 2018 to July 2019 were enrolled, and according to etiology detection results, they were divided into bacterial group with 57 children, viral group with 31 children, and mycoplasma group with 20 children. Related inflammatory markers were collected and compared between groups, including nCD64 index, whole blood white blood cell count (WBC), whole blood erythrocyte sedimentation rate (ESR), whole blood C-reactive protein (CRP), plasma D-dimer (D-D), and plasma procalcitonin (PCT) within 24 h after admission. The receiver operating characteristic (ROC) curve was plotted for nCD64 index and other inflammatory mar-kers in the diagnosis of bacterial CAP, and the area under the ROC curve (AUC), cut-off value, and the sensitivity, specificity, and accuracy of diagnosis were calculated. Results There were significant differences in nCD64 index and other inflammatory markers between the three groups (F=6.489-74.681,P<0.05), and compared with the viral group and the mycoplasma group, the bacterial group had significant increases in nCD64 index, whole blood WBC, whole blood ESR, whole blood CRP, plasma D-D, and plasma PCT (t=15.139-58.371,P<0.05). The ROC curve analysis showed that nCD64 index alone had a sensitivity of 94.7%, a specificity of 92.2%, and an accuracy of 93.5% in the diagnosis of bacterial CAP, and the combination of nCD64 index, whole blood CRP, and plasma PCT had a sensitivity of 96.5%, a specificity of 100%, and an accuracy of 98.1% in the diagnosis of bacterial CAP. Conclusion The nCD64 index has relatively high sensitivity, specificity, and accuracy in the diagnosis of bacte-rial CAP in children, and therefore, it has a high value in the etiological diagnosis of CAP.